Surgical management of gall bladder stones at tertiary care institute of Bhuj, Kutch, Gujarat - Rao, Gyaneshwar; Sukla, Rajesh; Rao, Aayushi (International Surgery Journal, 2019)
Background: Gallstones are the major cause of morbidity and mortality throughout the world. With at least 10 % of the adults have gallstones with a recent rise in the incidence due to change in the dietary factors. This study intends to know its various modes of presentation, treatment, and outcome. Methods: Fifty patients with symptoms and signs of cholelithiasis were included in the study, clinical profile, investigation, treatments, outcomes were analyzed. Results: The highest age incidence of cholelithiasis was in the 5th decade, more common in females. Pain abdomen was the most common symptom. Ultrasonography showed gallbladder stones in all patients and 52% of patients undergone open cholecystectomy, 48% of patients undergone laparoscopic cholecystectomy. The conversion rate of lap to open cholecystectomy was 4%. The operating room time and the length of post operative stay were 65 min and 7 days in open cholecystectomy and 115 min and 3 days in lap cholecystectomy. Conclusions: The result showed cholelithiasis was more common in females, 5th decade, presented most commonly with pain abdomen. Ultrasonography was the most common investigation. Laparoscopic cholecystectomy reduces the number of hospital days, pain disability.